2017
DOI: 10.1007/s10453-017-9471-9
|View full text |Cite
|
Sign up to set email alerts
|

Source regions of ragweed pollen arriving in south-western Poland and the influence of meteorological data on the HYSPLIT model results

Abstract: We have investigated the relationship between the inflow of air masses and the ragweed pollen concentration in SW Poland (Wrocław) for a 10-year period of 2005–2014. The HYSPLIT trajectory model was used to verify whether episodes of high concentrations can be related to regions outside of the main known ragweed centres in Europe, like Pannonian Plain, northern Italy and Ukraine. Furthermore, we used two different meteorological data sets (the global GDAS data set and from the WRF mesoscale model; the meteorol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
0
14
0
4
Order By: Relevance
“…Analysis of trajectories is widely used in order to identify the most probable location of air pollution sources (Cesari et al 2014;Godłowska et al 2015) as well as any pollen source location or movement (Smith et al 2005;Stach et al 2007;Bilińska et al 2017). The back-trajectories were used in a study conducted by Skjøth et al (2015) which investigated the source of Betula pollen in Wrocław and Worcester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of trajectories is widely used in order to identify the most probable location of air pollution sources (Cesari et al 2014;Godłowska et al 2015) as well as any pollen source location or movement (Smith et al 2005;Stach et al 2007;Bilińska et al 2017). The back-trajectories were used in a study conducted by Skjøth et al (2015) which investigated the source of Betula pollen in Wrocław and Worcester.…”
Section: Discussionmentioning
confidence: 99%
“…Model configuration in terms of physical parameterization is provided by Kryza et al (2017) and Ojrzyńska et al (2017). For the HYSPLIT model, only the meteorological information from the innermost domain was used, as the high spatial and temporal resolutions were found to be important for the pollen transport studies, as reported earlier by Bilińska et al (2017). The WRF model data were prepared for HYSPLIT using the arw2arl preprocessor.…”
Section: The Hysplit Modelmentioning
confidence: 99%
“…Не останнє місце у поши-ренні пилку амброзії посідає проблема глобального потепління та забруднення атмосферного повітря [6]. Також деякі дослідники доводять, що значну роль у зростанні кількості пилку в атмосферному повітрі ві-діграє перенесення пилкових зерен повітряними ма-сами на досить великі відстані [7]. Взагалі, кількість пилку у повітрі по днях палінації повинна відповіда-ти дозріванню пилку та проходити за нормальним (Гаусовим) законом.…”
Section: літературний оглядunclassified
“…Жовчнокам'яна хво-роба посідає третє місце після серцево-судинних зах-ворювань і цукрового діабету серед причин втрати працездатності та необхідності госпіталізації [7]. Епідеміологічні та клінічні дослідження свідчать, що жовчокам'яна хвороба частіше проявляється в жінок, ніж у чоловіків.…”
Section: вступunclassified
“…The transport of pollen from the south of Europe is especially visible in periods before the local pollen season starts in Central and Northern Europe (Ranta et al 2006;Skjøth et al 2007). Source regions of various pollens have been determined with the use of back trajectory from the HYSPLIT model (Makra et al 2010;Hernández-Ceballos et al 2014;de Weger et al 2016;Bilińska et al 2017). However, examples from Poland show that long-range transport plays a significant role in the concentrations of pollen that are rare in the Polish environment, especially Ambrosia Smith et al 2008;Kasprzyk et al 2011;Bilińska et al 2017).…”
Section: Introductionmentioning
confidence: 99%